The symbol of the apes power in the Kembang Dewa Retna play - Darmoko, Darmoko; Christian Briliyandi Pramaditra, Raden Mas (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
Purwa shadow puppets are divided into several ages, namely myths about the gods, Lokapala, Arjunasasrabahu, Ramayana, and Mahabharata. The Kembang Dewa Retna play is based on a story originating from the Ramayana period. The battle for primacy and outrage in the story is built through the plays performed by the dalang. This study discusses the relationship between symbols, power, and supernatural powers in the wayang kulit play of the Ramayana era entitled Kembang Dewa Retna by Ki Manteb Soedharsono. Flower of Dewa Retna as a manifestation of the power of the monkey which is manifested through Kapi Pramuja. This study aims to explain the struggle of ape forces against giant forces. This study uses an objective approach, qualitative descriptive method, and the theoretical conceptual framework of Javanese ethics from Franz Magnis Suseno. The results of this study indicate that the Flower of Dewa Retna is a symbol of the power of apes who have magical powers and struggle against anger. The power of the Kembang Dewa Retna bestowed by the gods to uphold virtue, truth, and justice.Keywords: symbol, power, magic, wayang kulit purwa, Javanese